The skull alphabet book. - Pallotta, Jerry (Watertown, MA : Charlesbridge Pub.., 2002)
Asks the reader to identify, by learning functions of facial bones and teeth, the skull of an animal for each letter of the alphabet.
K-3
Keywords: Skull--Juvenile literature; Alphabet books; Skull; Animals--Physiology.; Alphabet